Peningkatan Jiwa Enterpreneurship untuk mewujudkan Kemandirian Ekonomi pada Generasi Muda Desa Mananggu Kabupaten Boalemo Wilayah Pesisir Teluk Tomini - Wenny Hulukati; Maryam Rahim; Idriani Idris; Rena Madina (Universitas Negeri Gorontalo, 2023)
Young people in rural regions need to possess an entrepreneurial spirit as a mental strength that motivates them to be capable of starting a business. It can evade the unemployment problem, which the solutions has not found yet until present day. The goal of this community service program is to foster an entrepreneurial spirit in the youth of Mananggu Village, Boalemo Regency, Tomini Bay Coastal Region, in an effort to achieve economic independence. This program's particular objectives include encouraging young people to be more entrepreneurial by training them with skills based on village potential and providing an opportunity for students participating in the Developing Village Thematic KKN to solve societal issues. The outcomes of this activity include: (1) enhancing the youthful generation of Mananggu Village, Boalemo Regency, and Tomini Bay Coastal Region's entrepreneurial spirit and productive skills based on local potential; and (2) providing students participating in the Thematic Village Community Service Program with experience solving community problems.